The Influence of Game Media on Children's Knowledge and Attitudes in Diarrhea Prevention at SDN Kembang Tanjong Sub-District - Idarul Hafni (Journal of Social Research, 2023)
Diarrhea is an environment-based disease and occurs in almost all geographical areas in the world. Sustainable Development Goals (SDGs) are improvements to the Millennial Development Goals (MDGs). SDGs target number three, namely healthy and prosperous life, is to ensure a healthy life and improve the welfare of all people of all ages. The purpose of this study is to analyze the influence of snakes and ladders game media on children's knowledge in diarrhea prevention at SDN Kembang Tanjong District. This research is quantitative research with a quasi-experimental research design (pseudo-experiment) using a non-equivalent control group design. Gender. In this study, the results of frequency distribution based on the characteristics of respondents totaling 80 people were as many as 40 people (50%) were male and as many as 40 people (50%) were female. Based on the results of the distribution of efficiency based on class characteristics, as many as 16 people (20%) are in class IV (four), as many as 28 people (35%) are in class V (five) and as many as 36 people (45%) are in class VI (six). The results of the analysis using the Wilcoxon test with a confidence level of 95% using snake and ladder game media with a p-value of knowledge value of 0.000 ? 0.05 so that it can be concluded that there is an influence of health education with snakes and ladders game media on children's knowledge in preventing diarrhea in children at SDN Kembang Tanjong District.